(untitled) (Hungarian Journal of Industry and Chemistry, 2008)
In our work we focused on the effect of the microwave energy at the aerobic and anaerobic biological degradability of sewage sludge. The sewage sludge is a multiphase system with high water content. Because of the presence of water molecules sludge is able to absorb the microwave energy efficiently. Because of the variable dielectric properties the different component of sludge heat differently, these effects cause „thermal shock”. During the microwave treatment the configuration of macromolecules are varied and the cell walls of the microorganisms are opened by the thermal shock, it means the organic compounds are accessible for further biological degradable. In our experiments digested municipal sewage sludge and undigested dairy-sludge were used. Labotron 500 professional microwave equipment was used for the microwave treatment at 2450 MHz frequency. The specific microwave power level was changed between 1 to 5 W/g. Oxitop PM barometrical measurement system was used for determination of the biogas production at 40 °C, the measurement of the chemical oxygen demand (COD) of sludge was based on a potassinium-bichromate method, and a respirometric BOD meter was used for the biochemical oxygen demand (BOD) measurement (20 °C). Our results showed that, the microwave energy could be a practical and effective alternative technique to enhance the biodegradability of sludge, because after microwave treatment increases the biodegradability from 7 up to 40% by diary sludge and from 12 up to 48% by municipal sludge. It was found, that the originally resistant sludge after a microwave pre-treatment became more degradable, and its biogas production increased from 20-30 ml/g dry weight up to 500 ml/ gdry weight. The highest microwave power level effects the highest biogas yield, but the energy balance at lower specific power level (1-2 W/g) and longer treatment time gave just notable net energy production compared to the control sample.